RNA‐Seq identification of candidate defense genes targeted by endophytic Bacillus cereus‐mediated induced systemic resistance against Meloidogyne incognita in tomato. Issue 12 (26th July 2018) - Hu, Haijing; Wang, Cong; Li, Xia; Tang, Yunyun; Wang, Yufang; Chen, Shuanglin; Yan, Shuzhen
Abstract: BACKGROUND: The endophytic bacteria Bacillus cereus BCM2 has shown great potential as a defense against the parasitic nematode Meloidogyne incognita . Here, we studied endophytic bacteria‐mediated plant defense against M. incognita and searched for defense‐related candidate genes using RNA‐Seq. RESULTS: The induced systemic resistance of BCM2 against M. incognita was tested using the split‐root method. Pre‐inoculated BCM2 on the inducer side was associated with a dramatic reduction in galls and egg masses on the responder side, but inoculated BCM2 alone did not produce the same effect. In order to investigate which plant defense‐related genes are specifically activated by BCM2, four RNA samples from tomato roots were sequenced, and four high‐quality total clean bases were obtained, ranging from 6.64 to 6.75 Gb, with an average of 21 558 total genes. The 34 candidate defense‐related genes were identified by pair‐wise comparison among libraries, representing the targets for BCM2 priming resistance against M. incognita . Functional characterization revealed that the plant–pathogen interaction pathway (ID: ko04626) was significantly enriched for BCM2‐mediated M. incognita resistance. CONCLUSION: This study demonstrates that B. cereus BCM2 maintains a harmonious host–microbe relationship with tomato, but appeared to prime the plant, resulting in more vigorous defense response toward the infection nematode. © 2018 Society of Chemical Industry Abstract : This study focused on a defense‐related gene that triggered endophytic bacteria defense against a plant–parasitic nematode. The findings highlight good candidates for use in endophytic bacteria‐mediated crop protection.